2019
DOI: 10.1371/journal.pgen.1007975
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effects of germline exposure to environmental toxicants by high-throughput screening in C. elegans

Abstract: Chemicals that are highly prevalent in our environment, such as phthalates and pesticides, have been linked to problems associated with reproductive health. However, rapid assessment of their impact on reproductive health and understanding how they cause such deleterious effects, remain challenging due to their fast-growing numbers and the limitations of various current toxicity assessment model systems. Here, we performed a high-throughput screen in C . elegans to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 104 publications
5
57
0
Order By: Relevance
“…There is an urgent need for consistent and accurate HTS systems for rapid toxicity assessment of emerging NMs (Ban, Zhou, Sun, Mu, & Hu, ). The present study showed that the HTS strategy using C. elegans can be successfully applied for toxicity assessment of ENMs, as has been reported in previous studies on NMs and various environmental toxicants (Hunt et al, ; Jung et al, ; Mashock et al, ; Shin et al, ). The developmental and reproductive toxicity assay described in this study used the COPAS Biosort assay for counting the number and measuring the size of C. elegans at L1 larval and adult stages.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There is an urgent need for consistent and accurate HTS systems for rapid toxicity assessment of emerging NMs (Ban, Zhou, Sun, Mu, & Hu, ). The present study showed that the HTS strategy using C. elegans can be successfully applied for toxicity assessment of ENMs, as has been reported in previous studies on NMs and various environmental toxicants (Hunt et al, ; Jung et al, ; Mashock et al, ; Shin et al, ). The developmental and reproductive toxicity assay described in this study used the COPAS Biosort assay for counting the number and measuring the size of C. elegans at L1 larval and adult stages.…”
Section: Discussionsupporting
confidence: 82%
“…C. elegans growth assay is currently being used to screen the ToxCast Phase I and II libraries of the US Environmental Protection Agency (EPA), which comprise 1011 chemicals (Judson et al, ; Knudsen et al, ). In addition, the COPAS‐based C. elegans HTS assay has been used in the screening of neurotoxicants (Boyd, Smith, Kissling, & Freedman, ) and for assessing the reproductive toxicity of drugs and environmental chemicals (Maurer, Ryde, Yang, & Meyer, ), effects of environmental toxicants on germline cells (Shin, Cuenca, Karthikraj, Kannan, & Colaiácovo, ), larval growth and development (Boyd, et al, ), and chemical disruption of germline function (Allard, Kleinstreuer, Knudsen, & Colaiácovo, ). It has also been used for studying the mitochondrial function and morphology (Daniele et al, ) and developmental toxicity in axenic liquid cultures of C. elegans (Sprando, Olejnik, Cinar, & Ferguson, ), zebrafish, rats and rabbits (Boyd et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans has emerged as a powerful model organism to quantitatively assess the molecular mechanisms underlying the toxicity of environmental toxins and nanoparticles . In this study, we measured the adverse effects of GO and GONH 2 upon acute or chronic exposure on various behavioral traits.…”
Section: Resultsmentioning
confidence: 99%
“…elegans has emerged as a powerful model organism to quantitatively assess the molecular mechanisms underlying the toxicity of environmental toxins and nanoparticles. [27,60,61] In this study, we measured the adverse effects of GO and GONH 2 upon acute or chronic exposure on various behavioral traits. Fecundity was reduced upon chronic GO exposure, confirming studies in C. elegans using GO material based on a different protocol.…”
Section: Resultsmentioning
confidence: 99%
“…These unknown factors might include enzymes involved in HR or coordination of chromosome pairing (Goldman and Lichten, 1996;Grushcow et al, 1999;Goldman and Lichten, 2000;Shinohara and Shinohara, 2013;Shinohara et al, 2019), as well as exposure to chemicals that may possibly perturb some of these key meiotic processes (Shin et al, 2019;Cuenca et al, 2020). Therefore, sensitive cell-based assay systems able to recapitulate the LCR-mediated meiotic NAHR process experimentally are needed in order to identify the genes and environmental factors that can modulate recurrent CNV formation (Lupski, 2015;Yauk et al, 2015;Conover and Argueso, 2016).…”
Section: Introductionmentioning
confidence: 99%